(untitled) (Baghdad Science Journal, 2015)
The role of filamentous bacteria represented by Streptomycessp was studied as biological treatment for activated sludge AL- Restomia treatment unit in Baghdad city. The result shows reducing in phosphate concentration where apprise in started entrance the treatment unit 12.083 mg/L fast the unit stages reached to 8.426 mg /L where nitrate concentration apprises 3.59 mg/l and ending in 2.43 mg/L The concentration of ammonia apprises 1358 mg/L and reached to 140 mg/L. also the TDS concentration reduced from 1426 to 1203 mg/L where nutrient which represented (SO4, Mg, Ca, Na, K) reduced by range 30.883- 23.337 , 194- 121 , 440- 321 , 109.03- 101.53 and 16.85- 15.4mg/L respectively COD reduce from427.263- 82mg/L with absorbance0.018- 0.027 nm.